ผลกระทบของเงินทุนไหลเข้าที่มีต่อการออมในประเทศ : กรณีของประเทศไทยในช่วง 2518-2539 - วรวิทย์ พงษ์พิทักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The objective of the study in first part is to measure the degree of international capital mobility of Thailand both before and after financial liberalization in 1989. The result find that degree of international capital mobility of Thailand after financial liberalization has a higher level than before that from 0.23 to 0.43 or increase 87 %. It ‘ร indicate that Thailand has a higher open economic system. The objective of the study in second part is to test the relationship between net foreign capital inflows and gross investment, with gross national savings and savings by economic sectors. The results show that net foreign capital inflows have a positive impact on gross investment. เท contrast, that foreign capital inflows impact gross national savings in a negative sign. By economic sectors, the results find that net private foreign capital inflows have a negative impact to households’ s savings but impact on corporated businesses s savings and financial sectors s savings in a positive sign. Furthermore, net public foreign capital inflows impact government s savings in a negative sign. Thailand has a higher open economic system. Capital inflows continue increase. But from this result showed that net private foreign capital inflows impact households s savings in a negative sign. Since households s savings are the most important component in gross national savings and trend to be decline. So that government has to find the ways how to increase households s savings level pass through government s policy instruments.